Design of distance courses in a web learning environment : (WebLIDI) - Sanz, Cecilia Verónica
This paper presents some of the aspects related to the multidisciplinary research process initiated in III LIDI for the development of a learning environment focused on the WEB (WebLIDI). It attempts to gather, in a work group, the technology working logic and the basic notions about teaching and learning. This project not only aims at developing a distance course design methodology, but also at the possibility of applying it through the WebLIDI environment - based on the principles connected to the pedagogical and technological variables involved in teaching and learning instances. Some of the decisions taken throughout this process are here presented in detail, ranging from general information of a course to content structuring and evaluation possibilities. Also, the current state of the development - expected to be used experimentally as from the second semester of 2003- is specified.